2019
DOI: 10.1111/jcpt.12816
|View full text |Cite
|
Sign up to set email alerts
|

Cancellations of elective surgical procedures due to inadequate management of chronic medications

Abstract: Summary What is known and objectives Inadequate management of chronic medication puts patients at risk and causes unnecessary suspension of surgical procedures. The objective of the study was to calculate the rate of cancellation of elective surgical procedures due to inadequate management of chronic medications and to analyse the underlying causes of cancellation. Methods We designed an analytic, observational, retrospective study of all elective surgical procedures performed from July to October 2017 in a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Among the articles reviewed, the two most frequent years of publication were 2018 (Brown et al, 2018; Dries, 2018; Wyatt et al, 2018) and 2020 (Derseh et al, 2020; da Silva Schulz et al, 2020; Vogl et al, 2015) ( n = 3), followed by 2012 (Husted, 2012; Johansson Stark et al, 2014), 2015 (Crump et al, 2015; Liederbach et al, 2015) ( n = 2), 2011 (Papadopoulos et al, 2016), 2014 (Ayyadhah Alanazi, 2014), 2016 (McClurkin & Smith, 2016), 2017 (Pettersson et al, 2017) and 2019 (de Lorenzo‐Pinto et al, 2019). None of these articles were published in 2013 or 2021 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the articles reviewed, the two most frequent years of publication were 2018 (Brown et al, 2018; Dries, 2018; Wyatt et al, 2018) and 2020 (Derseh et al, 2020; da Silva Schulz et al, 2020; Vogl et al, 2015) ( n = 3), followed by 2012 (Husted, 2012; Johansson Stark et al, 2014), 2015 (Crump et al, 2015; Liederbach et al, 2015) ( n = 2), 2011 (Papadopoulos et al, 2016), 2014 (Ayyadhah Alanazi, 2014), 2016 (McClurkin & Smith, 2016), 2017 (Pettersson et al, 2017) and 2019 (de Lorenzo‐Pinto et al, 2019). None of these articles were published in 2013 or 2021 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This cut‐off point was established of based on reference manuscripts, avoiding fractional numbers. Finally, therefore, 15 articles were included in our literature review (Ayyadhah Alanazi, 2014; Brown et al, 2018; Crump et al, 2015; Derseh et al, 2020; Dries, 2018; Husted, 2012; Johansson Stark et al, 2014; Liederbach et al, 2015; de Lorenzo‐Pinto et al, 2019; McClurkin & Smith, 2016; Papadopoulos et al, 2016; Pettersson et al, 2017; da Silva Schulz et al, 2020; Vogl et al, 2015; Wyatt et al, 2018) (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…6 Effective strategies to address and mitigate these will vary, and institutions need data to inform their decisions. 7 Cancelation of pediatric procedures carries many costs to children and families-as we have identified-as well as to the health system. While some cancelations may be inevitable, such as those caused by unpredictable fitness for surgery or urgent demands for hospital resources, it is crucial to identify risk factors for cancelation in order to minimize the frequency as well as the impact on families and services, particularly as there are suggestions that cancelation of children's surgeries are an increasing problem.…”
Section: Discussionmentioning
confidence: 95%
“…The reasons for and impact of surgical cancelations are complex and variable between institutions 6 . Effective strategies to address and mitigate these will vary, and institutions need data to inform their decisions 7 . Cancelation of pediatric procedures carries many costs to children and families—as we have identified—as well as to the health system.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the perioperative patients have a history of taking chronic medications [1]. Many studies have shown that inadequate preoperative management of chronic medications not only places patients at risk but also causes unnecessary delays in surgical procedures [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%